2018
DOI: 10.3390/ijerph15112442
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Suicide in Young Men in Greenland: A Systematic Review

Abstract: Suicide is the leading cause of death among young men aged 15–29 in Greenland, but few epidemiological studies have described this problem. We aimed to summarise descriptive epidemiological studies of suicide in young men in Greenland compared with other demographic groups in Denmark and Greenland to inform future suicide prevention strategy. We searched PubMed, PsycINFO, and Embase using an agreed search strategy to identify English-language papers describing suicide epidemiology in Greenlandic men aged 15–29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
3
4
0
1
Order By: Relevance
“…The findings of this paper are in line with previous epidemiological studies of suicides in Greenland. A systematic review that investigated epidemiological factors of suicide among young men in Greenland found the same increase in suicide rates as were shown in the analyses of period rates in the current study [30]. The results on suicide rates according to age and sex are in accordance with previous findings where youth aged 15 to 24 years have the highest rates across all age groups while young men have the highest rates overall [6,31].…”
Section: The Epidemiology Of Suicide In Greenlandsupporting
confidence: 91%
“…The findings of this paper are in line with previous epidemiological studies of suicides in Greenland. A systematic review that investigated epidemiological factors of suicide among young men in Greenland found the same increase in suicide rates as were shown in the analyses of period rates in the current study [30]. The results on suicide rates according to age and sex are in accordance with previous findings where youth aged 15 to 24 years have the highest rates across all age groups while young men have the highest rates overall [6,31].…”
Section: The Epidemiology Of Suicide In Greenlandsupporting
confidence: 91%
“…The gender differences in methods of suicide attempts described in the present study are consistent with recent studies which found a higher prevalence of intoxication among women and more violent methods among men [ 14 , 26 , 42 ]. This points to the need for restricting the availability of different means typically used for attempting suicide.…”
Section: Discussionsupporting
confidence: 92%
“…Being male was considered an important predictor for cocaine use, confirming the findings of one systematic review [ 25 ]. According to a study conducted in a Canadian hospital [ 26 ], there was a high prevalence of males (73.2%) and cocaine use (91.5%) in suicide attempts among drug users.…”
Section: Discussionsupporting
confidence: 77%